Nursing care for premature newborns in a specialized center: experience report (Research, Society and Development, 2020)
Objective: To report the experiences lived by nursing students in a specialized care center for child and adolescent health. Method: Descriptive study, of the experience report type, of nursing students from a university in northern Rio Grande do Sul/Brazil, with the practice in the subject of Nursing Curricular Internship in a Specialized Center for Child and Adolescent Health, from August 19 to September 14, 2020. Results: During childcare consultations, it was possible to perform active listening with the mother, to answer doubts and to provide orientations that contribute to the healthy growth and development of premature children. Experiencing prematurity in the family is a delicate moment that needs attention and care from health professionals, especially nurses. Thus, it was possible to develop a humanized care for the child and family, providing support from the multidisciplinary team. Conclusion: It is essential that health professionals recognize feelings that may emerge in the family experiencing prematurity. Through the childcare consultation, it is possible to provide a safe environment, use care strategies, such as active listening, welcoming dialogue, answering doubts, guiding and thus preventing possible complications.